Dos interpretaciones ramistas de Hor,. Carm, 3,1, en el humanismo renacentista - Merino Jerez, Luis (1992)
Cl. Mignault and Francisco Sánchez de las Brozas, El Brocense, apply the Ramist theory of the analysis in their observations on Hor., Carm., 3,I. On establishing the quaestio, the two humanists reach diferent interpretations, both in the expression and in the concept. C1. Mignault summarizes the content of the poem in sequences which follow one another chronologically and carries ont a religious reading of the text: the serenity of the spirit (animi tranquillitas) is the only means of achieving the uita beata. Francisco Sánchez avoids the Christian reading andproposes a rational interpretation in the manner of syllogism: we must aim at uita tenuis because it is only way of life whichprovides us with a tranquil life (uita tuta).
Keywords: Sánchez de las Brozas, Francisco, -- 1522-1600; Mignault, Claude, -- 1536-1606; Horacio Flaco, Quinto; Humanismo; Renacimiento